Antiepileptic Drug Selection According to Seizure Type in Adult Patients with Epilepsy - Kim, Hyeyun; Kim, Dong Wook; Lee, Soon-Tae; Byun, Jung-Ick; Seo, Jong-Geun; No, Young Joo; Kang, Kyung Wook; Kim, Daeyoung; Kim, Keun Tae; Cho, Yong Won; Yang, Kwang Ik (Journal of clinical neurology (Seoul, Korea), 2020)
Epilepsy is a common neurological disorder that is mainly treated using antiepileptic drugs. Several antiepileptic drugs such as phenobarbital, phenytoin, primidone, and ethosuximide were developed in the early 20th century. More than 10 types of antiepileptic drugs have been developed since the 1990s, and there are now more than 20 antiepileptic drugs in active clinical use. The choice of antiepileptic drugs is based on the clinical features of the seizure types, electroencephalogram findings, epileptic syndrome, and drug stability. Currently there are 19 antiepileptic drugs approved by the Korean Food and Drug Administration, 18 of which (with the exclusion of brivaracetam) are covered by the National Health Insurance Service in Korea. We reviewed the selection of antiepileptic drugs according to the classification of epileptic seizures.Epilepsy is a common neurological disorder that is mainly treated using antiepileptic drugs. Several antiepileptic drugs such as phenobarbital, phenytoin, primidone, and ethosuximide were developed in the early 20th century. More than 10 types of antiepileptic drugs have been developed since the 1990s, and there are now more than 20 antiepileptic drugs in active clinical use. The choice of antiepileptic drugs is based on the clinical features of the seizure types, electroencephalogram findings, epileptic syndrome, and drug stability. Currently there are 19 antiepileptic drugs approved by the Korean Food and Drug Administration, 18 of which (with the exclusion of brivaracetam) are covered by the National Health Insurance Service in Korea. We reviewed the selection of antiepileptic drugs according to the classification of epileptic seizures.